Forming coalitions: the case of Brazil in the brics - Doval, Gisela Pereyra (2015)
This article examines the importance of belonging to a group that puts pressure internationally through a coalition pursuing similar goals. The process of coalition building has been central in Brazil’s multilateral negotiations to balance the centre-periphery forces, but also with regard to the possibilities that this country has of belonging to the club of the powerful. We hold that the BRICS group is a step in Brazilian ambitions towards that end. We also emphasize the common views and differences of these five countries at multilateral level. The aim of this article is to analyse Brazil’s strategy of coalition building to understand what kind of coalition the so-called BRICS countries form and ascertain the advantages and disadvantages of Brazil’s participation in it.